A Note on Economies of Scale - Walters, A. A. (The Review of Economics and Statistics, 1963)
1. The theoretical foundations of the aggregate production function give one grounds for doubting whether the concept is at all useful. Nevertheless, the temptation to discuss movements in indices of input and output in terms of such a function is difficult to resist. And there is no doubt that it is useful to rationalize the data along these lines. In his analysis of the aggregate production function in the United States, Solow derived many useful results.1 These findings, however, depended on the assumption of constant returns to scale in the aggregate production function. This assumption simplified the analysis considerably. Solow found the capital coefficient a, in the Cobb-Douglas, from the proportion of income going to capital; then, by subtracting from output per unit of capital (X/K) the product of (1 a) and capital per